The Impact of Consumer versus Firm Credit on Economic Growth - Sami Al Rahamneh, Sara (Jordan Journal of Business Administration, 2023)
This study investigates the impact of consumer versus firm lending on Jordanian economic growth by using quarterly data from 1994 to 2018. This study uses the Autoregressive Distributed Lag (ARDL) model. The empirical results show that there is a positive and long-run equilibrium relationship between consumer lending and GDP growth, since increasing consumer lending raises consumption of services, which contributes 66.6% of Jordan's GDP. Furthermore, the empirical results show that there is no long-run equilibrium relationship between firm lending and Jordanian economic growth. The researcher attributes these results to the crowding effect of government lending. The empirical results show that there is a negative and long-run equilibrium relationship between government lending and GDP growth, as more government lending will decrease the number of loans to the business sector, which in turn will affect the economic growth negatively.